Analisis muatan nilai-nilai karakter dalam buku teks sejarah Indonesia tingkat SMA kelas XI terbitan Kemendikbud dan Erlangga - Imas Siti Masitoh; Ajat Sudrajat (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The research is aimed to analyse character education content and the factors that led to the similarities and differences in character education content of Indonesian history textbooks of Grade XI students based on 2013 curriculum issued by the Ministry of Education and Culture and Erlangga. Problems in this research were examined using a descriptive qualitative research with content analysis method. Results of the study show that textbooks issued by Ministry of Education and Erlangga contain the character values that are in the National Character Education and PPK. Ministry of Education’s textbook has four dominant character values, namely a sense of wonder, nationalism, being independent, and religiousity. While character values in Erlangga textbook is more dominant on the following values: fond of reading, a sense of wonder, nationalism, and integrity. The textbooks issued by Ministry of Education and Erlangga both have such character values because they referred to the 2013 Curriculum, which emphasizes the development of individuals’ characteristic. The factors that caused the difference in the contents of character values in the both of these textbooks are the approach and the material’s form of delivery. The Ministry of Education and Culture's textbook used a regressive approach while Erlangga’s textbook used the narrative approach.Each book raises the character value with different forms of delivery, either directly or directly. The content of character values in these textbooks are expected to be sources of character growth for students and to help them play a role in efforts to develop character education in history studies.